Detectable land use impact on methanotrophs and methanogens in kettle hole sediments but not on net methane production potentials - Kynast, Danica; Reverey, Florian; Ganzert, Lars; Grossart, Hans-Peter; Lischeid, Gunnar; Kolb, Steffen (FEMS microbiology ecology, 2025)
Kettle holes (KHs) are dynamic freshwater systems and potential sources of the greenhouse gas methane. Due to their small size (<1 hectare), KHs are subject to inorganic and organic matter input from their terrestrial surroundings, governed by land use. Matter inputs include inorganic solutes that are alternative electron acceptors and impact on methanotrophs and methanogens. Thus, they might affect methane net production. We sampled 10 kettle hole sediments embedded in landscapes with either agricultural or forest land use and determined their (i) potential net methane production rates, (ii) the composition of their microbial communities, and (iii) physicochemical soil parameters. Potential net methane production did not significantly differ by land use type but between single KHs. However, land use type had a strong impact on methanotroph and methanogen and on total bacterial and archaeal microbiota structure. Relative abundances of methanotrophs and methanogens were significantly higher in agricultural KHs, and their relative abundances were among the most influential variables projecting net methane production potentials along with nutrient status and water content. Land use type was thus identified as a major factor that impacts the structure and biodiversity of general and methane-cycling microbiota, but it did not affect net methane production potentials.